From Jurisprudence to Algorithms: The Role of Artificial Intelligence in Contemporary Sharia Financial Decision-Making - Edi Mulyono; Mahmoud Mohamed Ali Mahmoud Edris (PT. Islamic Research Publisher, 2025)
Non Index Publication